Radiocarbon age of seven cores from the Araplı catchment in the Pergamon Micro-Region, western Turkey - Joris Starke; Brigitta Schütt; Moritz Nykamp; Robert Busch; M Doğan; Fabian Becker (PANGAEA, 2025)
The dataset was collected from seven sediment cores along a transect spanning the Araplı alluvial fan, east of ancient Pergamon, in the eastern lower Bakırçay plain, Pergamon micro-region, Türkiye. The cores were taken, described, sampled, and analyzed in the field and at the Bergama excavation house in October 2023. Sediment samples were taken at irregular intervals and orientated along layer boundaries; samples include 3 cm of sediment in fine earth and 5 cm in gravelly material. Reported sample depths are simplified and given by their mean depth. Results of radiocarbon dating of samples taken from the cores are presented.
In: Starke, J et al. (2025): Sediment analyses (pH, electrical conductivity, mag. susceptibility, loss on ignition, remission and pXRF) and radiocarbon ages from the Araplı catchment in the Pergamon Micro-Region, western Turkey [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.983469